Shiite Geopolitics Contemporary Shiite Geopolitical Theories and Terms - Safi, Bayan Al (International Journal of Scientific Research and Management (IJSRM), 2020)
Ideological doctrinal theories were developed specifically for Shiite geopolitics as the basis for the implementation of the Iranian expansionist strategy and attempts to make the Iranian sectarian project successful by controlling the countries located in its vital area. In the first decade of the Islamic revolution, Shiite geopolitical theories were based on Iran's outing its geographical borders and turning it into the axis of the Islamic world. Thus, Tehran took a liberty of reaching out to social, cultural and sectarian components in other countries with the aim of building Muslim Shiite regimes under the leadership of Iran.The paper examines the manifestation of the return of geopolitics in the 21st century, in particular, the Iranian Shiite geopolitics. The expansion of Shiite political Islam, especially after the Iranian role demonstrated the terrorist-armed aspect of sectarianism.